Subtype switching in breast cancer brain metastases: a multicenter analysis. Issue 8 (23rd January 2020) - Hulsbergen, Alexander F C; Claes, An; Kavouridis, Vasileios K; Ansaripour, Ali; Nogarede, Claudine; Hughes, Melissa E; Smith, Timothy R; Brastianos, Priscilla K; Verhoeff, Joost J C; Lin, Nancy U; Broekman, Marike L D
Abstract: Background: Breast cancer (BC) brain metastases (BM) can have discordant hormonal or human epidermal growth factor receptor 2 (HER2) expression compared with corresponding primary tumors. This study aimed to describe incidence, predictors, and survival outcomes of discordant receptors and associated subtype switching in BM. Methods: BCBM patients seen at 4 tertiary institutions who had undergone BM resection or biopsy were included. Surgical pathology reports were retrospectively assessed to determine discordance between the primary tumor and the BCBM. In discordant cases, expression in extracranial metastases was also assessed. Results: In BM from 219 patients, prevalence of any discordance was 36.3%; receptor-specific discordance was 16.7% for estrogen, 25.2% for progesterone, and 10.4% for HER2. Because estrogen and progesterone were considered together for hormonal status, 50 (22.8%) patients switched subtype as a result; 20 of these switches were HER2 based. Baseline subtype predicted switching, which occurred in up to 37.5% of primary HR+ patients. Moreover, 14.8% of initially HER2-negative patients gained HER2 in the BM. Most (63.6%) discordant patients with extracranial metastases also had discordance between BM and extracranial subtype. Loss of receptor expression was generally associated with worse survival, which appeared to be driven by estrogen loss (hazard ratio = 1.80, P = 0.03). Patients gaining HER2 status ( n = 8) showed a nonsignificant tendency toward improved survival (hazard ratio = 0.64, P = 0.17). Conclusions: In this multicenter study, we report incidence and predictors of subtype switching, the risk of which varies considerably by baseline subtype. Switches can have clinical implications for prognosis and treatment choice.